Objective and subjective variables in two university classes - Valdeón García, Roberto Antonio (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2000)
The importance of the motivational components in the learning of foreign languages has attracted the interest of teachers, linguists and psychologists in recent decades, giving way to a number of acclaimed studies led by the Canadian psychologist Gardner and his associates. His theories, stressing the role of integrative motivation as a key element in successful language learning, aroused the interest of education researchers, who stressed the need to extend the field of research and include educational factors as well as socio-psychological ones. Oxford & Ehrman in the United States and Dörnyei in Europe have introduced new elements for consideration, and the latter has backed his theories with data emerging from Hungarian classrooms. In the present article we aim to underline the need to consider, on the one hand, the connections between objective variables, associated with the formal learning situation, such as class attendance and participation as well as results in language and other related subjects, and, on the other, affective variables in order to assess the importance of motivation in the language classroom.